2018
DOI: 10.3390/ani8040047
|View full text |Cite
|
Sign up to set email alerts
|

Did Harvey Learn from Katrina? Initial Observations of the Response to Companion Animals during Hurricane Harvey

Abstract: Simple SummaryWhen Hurricane Harvey struck the Gulf states in 2017, a large-scale rescue effort was launched by officials and citizens to rescue both people and animals. Over a decade since Hurricane Katrina (2005), this study explores whether the reforms to afford better protection to companion animals such as the Pet Emergency and Transportation Standards Act 2006 have made a difference. Key officials from various organizations within the state of Texas were interviewed and it was found that though there has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…It is clear that the animal disaster rescue laws in New Zealand are not fit for purpose and have significant limitations. Though there has been some criticism of the PETS Act 2006 being described as "no carrot and no stick" [1] and having some deficiencies [20,21], the passage of this law has been labelled as "effective" [22] and having positively influenced the culture within emergency management to afford greater protection to animals during and following disaster [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that the animal disaster rescue laws in New Zealand are not fit for purpose and have significant limitations. Though there has been some criticism of the PETS Act 2006 being described as "no carrot and no stick" [1] and having some deficiencies [20,21], the passage of this law has been labelled as "effective" [22] and having positively influenced the culture within emergency management to afford greater protection to animals during and following disaster [1].…”
Section: Discussionmentioning
confidence: 99%
“…The current animal disaster legal framework in New Zealand is based primarily upon the Animal Welfare Act 1999 and Civil Defence Emergency Management Act 2002. Both of these were written prior to Hurricane Katrina (2005) which was the genesis for modern animal disaster law with legislation being swiftly passed due to lessons identified, such as the Pets Evacuation and Transportation Standards (PETS) Act 2006 [1]. According to the Fritz Institute [2], 44% of those who chose not to evacuate during this catastrophic event did so in part because they were unable to take their pets as the federal policy was to leave pets (companion animals) behind at that time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, after Hurricane Katrina in 2005, the United States passed the Pets Evacuation and Transportation Standards Act. This policy requires state and local urban emergency management to consider and provide services for companion animals, which directly reduced the harm to people and companion animals when Hurricane Harvey occurred 12 years later ( Glassey, 2018 ).…”
Section: Urban and Companion Animalsmentioning
confidence: 99%
“…Leonard and Scammon ( 2007 ) provide an interesting review on changes in societal views of pets that may have contributed to the enactment of the PETS Act. Through interview surveys carried out in Texas following Hurricane Harvey in 2017, Glassey ( 2018 ) found that the PETS Act and the lessons of Hurricane Katrina had a positive effect for companion animals in the disaster response.…”
Section: Disasters and Animalsmentioning
confidence: 99%